2017
DOI: 10.2175/106143016x14798353399494
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Sustainability Indicators for Small to Medium Sized Urban Water Systems Using Fuzzy‐ELECTRE

Abstract: This paper investigates a novel simulation-optimization (S-O) framework for identifying optimal treatment levels and treatment processes for multiple wastewater dischargers to rivers. A commonly used water quality simulation model, Qual2K, was linked to a Genetic Algorithm optimization model for exploration of relevant fuzzy objective-function formulations for addressing imprecision and conflicting goals of pollution control agencies and various dischargers. Results showed a dynamic flow dependence of optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…(iv) Hydraulic Infrastructure. 13.3% of the publications handle with the sustainability of different hydraulic infrastructures, such as dams [76][77][78], urban drainage [79][80][81], sewerage systems [82], and water supply systems [83][84][85][86]. (v) Transport Infrastructure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(iv) Hydraulic Infrastructure. 13.3% of the publications handle with the sustainability of different hydraulic infrastructures, such as dams [76][77][78], urban drainage [79][80][81], sewerage systems [82], and water supply systems [83][84][85][86]. (v) Transport Infrastructure.…”
Section: Resultsmentioning
confidence: 99%
“…25.3% of the analysed manuscripts take into consideration the generation of waste resulting from the industrial processes involved in the production of construction materials or from the demolition works. Consideration is given to both solid wastes from construction materials [22,26] and water wastes [86]. Land use is an environmental concept that implies both land occupation and transformation of land.…”
Section: Environmental Criteriamentioning
confidence: 99%
“…There are many methods to aggregate information, among which simple additive weighting (SAW) [44] is commonly used. Other aggregation methods are used in city sustainability evaluation as well, such as the weighted geometric average (WGA) method [45], the order preference by similarity to ideal situation (TOPSIS) method [46][47][48] and others [49][50][51][52]. Different methods embodies different evaluation purposes, such as highlighting the advantage indicator, highlighting the disadvantage indicator, reflecting the distance between the indicator and the optimal or worst indicator, etc.…”
Section: Related Work On City Sustainability Evaluationmentioning
confidence: 99%
“…Yi et al develop the deviation maximization weighting method to observe the sustainable levels of 17 cities in Shandong Province, China [11]. Several studies on city sustainability evaluation can be found, and the related literature can be grouped into three categories, i.e., evaluation indicators selection [19][20][21][22][23][24][25][26][27][28], indicators' weights setting [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and information aggregation [44][45][46][47][48][49][50][51][52]. A detailed review of the related work is shown in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…In a TBL assessment, environmental impacts may be assessed using an LCA model (Chhipi-Shrestha et al, 2017;Godskesen et al, 2013;Rygaard et al, 2014) or environmental criteria selected on the basis of the project and region (Rathnayaka et al, 2016). Social impacts of water management can include factors that impact the public and employees, such as public acceptance or the risk of exposure to pathogens (Garcia and Pargament, 2015;Makropoulos et al, 2008;Rygaard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%